Interrelation of Zakat Literacy, Social Behavior and Perceived Value on Intention of paying Zakat - Pratiwi Ar, Dhita; Salam, Karta Negara; B, Ceskakusumadewi; Rizal, Muhammad; Panus, Panus (International Conference on Islamic Economic (ICIE), 2024)
: Through data from Puskas Baznas (2022), measurement results in the Sulawesi Region were found in general, the value of the Zakat Literacy Index in 2020 falls into the literacy level category moderate, namely 65.73 where the value of basic understanding gets a score of 71.30 (literacy level moderate) and the value of advanced understanding of zakat is included in the literacy level category the low is 55.40. It can be concluded that in the Sulawesi Region the level pRespondents' understanding of aspects of basic knowledge falls into the sufficient category baik, but the respondents' understanding of the aspects of zakat management in the institution official zakat is still relatively low. The purpose of this research is to find out whether Zakat literacy affects the intention to give zakat, how does social behavior influence the intention of paying zakar, then to find out the perceived value as a mediating variable affect the intention to tithe. This research is an associative quantitative, with non-technical probability sampling. The object of this research is muzakki with different backgrounds in Makassar which is easy to reach. Respondents were rounded up to 100 people collected through a questionnaire, with an ordinal scale, which is distributed to respondents to determine literacy, social behavior, perceived value and intention of muzakki. Data analysis method used in this study moderation uses SmartPLS by entering all data and tested convergent validity, discriminant validity, and significance test.